A STUDY ON CUSTOMER AWARENESS LEVEL AND SATISFACTION OF HEALTH INSURANCE POLICIES IN CHENNAI CITY - Chitra, Vijaya; Ramya, V.; Gajenderan, Vijayakumar (International Journal of Research -GRANTHAALAYAH, 2021)
The study proposed to examine product awareness of health insurance products on their satisfaction among the customers in Chennai city. The study employed primary and secondary data. The primary data is collected from the customers of health insurance policyholders in Chennai city. The responses are gathered from the policyholders through the well-designed questionnaire copy. The purpose of the secondary data is to familiarize the research area. The secondary information is collected from the research articles, magazines, Insurance Regulatory Development Authority, and daily newspapers. The study used a convenience sampling method. Overall, 300 questionnaires are distributed, out of which the customers return 283 filled responses. The filled answers are checked and finalized the entire 283 samples for the final study. Therefore, the total sample size of the study is 283. The study used frequency distribution, one-sample t-test, and General Linear Model of Multivariate Tests. The study confirmed that the customers are well aware of the health insurance companies and their products. The study also creates a significant relationship between awareness about health insurance products and the level of satisfaction